Prostate‐specific membrane antigen‐targeted photoacoustic imaging of prostate cancer in vivo. Issue 9 (28th June 2018) - Zhang, Haichong K.; Chen, Ying; Kang, Jeeun; Lisok, Ala; Minn, Il; Pomper, Martin G.; Boctor, Emad M.
Abstract : A sensitive, noninvasive method to detect localized prostate cancer, particularly for early detection and repetitive study in patients undergoing active surveillance, remains an unmet need. Here, we propose a molecular photoacoustic (PA) imaging approach by targeting the prostate‐specific membrane antigen (PSMA), which is over‐expressed in the vast majority of prostate cancers. We performed spectroscopic PA imaging in an experimental model of prostate cancer, namely, in immunocompromised mice bearing PSMA+ (PC3 PIP) and PSMA− (PC3 flu) tumors through administration of the known PSMA‐targeted fluorescence agent, YC‐27. Differences in contrast between PSMA+ and isogenic control tumors were observed upon PA imaging, with PSMA+ tumors showing higher contrast in average of 66.07‐fold with 5 mice at the 24‐hour postinjection time points. These results were corroborated using standard near‐infrared fluorescence imaging with YC‐27, and the squared correlation between PA and fluorescence intensities was 0.89. Spectroscopic PA imaging is a new molecular imaging modality with sufficient sensitivity for targeting PSMA in vivo, demonstrating the potential applications for other saturable targets relevant to cancer and other disorders. Abstract : A sensitive, noninvasive method to detect localized prostate cancer, particularly for repetitive study in patients undergoing active surveillance, remains an unmet need. We propose a photoacoustic (PA) imaging approach by targeting the prostate‐specific membrane antigen (PSMA), which is over‐expressed in the vast majority of prostate cancers. Through in vivo demonstration on an experiment with mice model, spectroscopic PA imaging can visualize the targeted agent, YC‐27, that binds on PSMA+ tumor.